(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The issue of land holding has always been a matter of concern in Assam for researchers, academicians and politicians. For this particular study, the period of 1946-57 has been chosen as it was the period of transition and the period of First General Election . Apart from that , this was the period when Assam witnessed the growth of population due to the massive influx of Refugees to the state. In this context, the Assam Land and Revenue Regulation, 1886 can be considered a landmark legislation. Several important Acts and Amendments were made during this period on the issue of land and agriculture. For example The Assam Land and Revenue Act, Assam Adhiars Protection and Regulation Act, Assam Land Acquisition and Requisition Act, Assam State Acquisition of Zamindari Act etc. The paper tries to discuss the acts and the debates from the theoretical perspective of Representation in connection with the Acts. Therefore the paper will try to focus on the discussions that took place in the Assam Legislative Assembly to analyse the nature of debate and several crucial Amendment Acts on Land in Assam. Besides this , the paper is also an attempt to see the nature of Representation of people’s demands and the execution of policies.